Investigating Balancing Control of a Standing Bipedal Robot With Point Foot Contact. Issue 21 (2016) - Ding, B.; Plummer, A.; Iravani, P.
Abstract: Comparing with wheeled or tracked moving machines, legged robots have potential advantages, especially when considering moving on discontinuous or rough terrain. For many bipedal robots, balance in the standing position is easy to maintain by having sufficient contact area with the ground. For some bipedal robots, the Zero Moment Point (ZMP) control method has been successfully implemented in which the center of mass is aligned above the support area. However, the balancing issue while standing becomes challenging when the contact area is very small. This paper presents a controller which is developed to balance a bipedal robot with coupled legs which have point foot contact. It is necessary to investigate the non-linear characteristics of the system. A pole-placement control method is used, and noise issues with sensing higher motion derivatives are investigated. The simulation-based evaluation indicates limitations that need to be addressed before experimental implementation.